A systematic review of dyadic approaches to reminiscence and life review among older adults. (2nd September 2019) - Ingersoll-Dayton, Berit; Kropf, Nancy; Campbell, Ruth; Parker, Michael
Abstract: Objective: This paper describes a systematic review of quantitative and qualitative studies that examine the effectiveness of dyadic approaches to life review and reminiscence. Methods: The search process began with 1, 056 potentially eligible articles and, after a multi-step screening process, led to 20 full-text articles for review. Results: The resulting studies (ten quantitative, nine qualitative, and one mixed-method) comprised six different kinds of dyadic approaches. There are a combination of benefits and problems associated with dyadic life review and reminiscence approaches. Conclusions: This review provides initial understanding of the impact of life review and reminiscence when care recipients and caregivers participate in the intervention together. Future clinical studies on dyadic approaches to life review and reminiscence should provide clearer descriptions of their protocols, include more consistent measures (incorporating in-the-moment measures), and involve populations of healthy older adults and their partners as well as those with cognitive impairment. The inclusion of qualitative studies helps interpret the diverse results reported in the quantitative studies and highlights key themes related to participating in dyadic interventions.